2022
DOI: 10.2147/nrr.s367050
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Perceived Responsibilities, and Associated Factors Regarding Colostomy Care Among Nurses Working in Surgical Units at Amhara Region General and Referral Hospitals, Ethiopia: A Mixed Method Study

Abstract: Background: Colostomy is one of the commonest lifesaving procedures worldwide with aims of decompression of an obstructed colon or diversion of feces. Colostomy care is important to improve the quality of life of the patient, yet information is scarce concerning knowledge, attitude, and role of nurses on colostomy care in Ethiopia generally and in Amhara region specifically. Objective: This study aimed to assess knowledge, attitude, perceived responsibility, and associated factors regarding colostomy care amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the other hand, only a small percentage 25 (7.4%) demonstrated high knowledge of colostomy care. Furthermore, the study conducted in Amhara regional hospitals found that only 40.4% of nursing participants had adequate knowledge of colostomy care ( Lebona et al, 2016 ; Tiruneh et al, 2022 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…On the other hand, only a small percentage 25 (7.4%) demonstrated high knowledge of colostomy care. Furthermore, the study conducted in Amhara regional hospitals found that only 40.4% of nursing participants had adequate knowledge of colostomy care ( Lebona et al, 2016 ; Tiruneh et al, 2022 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…First, SCNs are on the frontline of ostomy care in OCCs and have a key role in care provision to patients with colostomy, but they do not consider themselves responsible for colostomy care due to their limited knowledge about their roles, which roots in ambiguities in the concept of CNC. [ 28 29 30 ] Second, expressions such as ostomy care, colostomy care, and ileostomy nursing are interchangeably used, while patients with each type of ostomy have unique needs and all of them need long-term care and specific attention. [ 31 ] Nonetheless, to the best of our knowledge, there is no specific concept analysis study on the concept of CNC.…”
Section: Introductionmentioning
confidence: 99%